Presentasi Diri dan Praktik Hustle Culture pada Mahasiswa - Novita Sari, Anadea; Abidin, Zainal.; Poerana, Ana Fitriana (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research is motivated by the hustle culture phenomenon which is now starting to spread among university students. In this study, researchers tried to discuss the hustle culture phenomenon from a student's point of view. This study uses a qualitative method with a phenomenological approach. The theory used in this study is the theory of phenomenology according to Alfred Schutz and the theory of self presentation. The purpose of this research is to find out how communication experience is, what are the meanings and motives of Communication students at Singaperbangsa Karawang University to experience a hustle culture by participating in various activities outside of their lecture activities such as being active in campus organizations, activities and/or work while studying. The results of the study stated that there were differences in communication experiences, meanings and motives that were known from informants, including the communication experiences experienced, namely: positive communication experiences, experienced by informants while undergoing a hustle culture, communication experiences before and after undergoing a hustle culture, reduced communication experience during breaks and interactions with friends and family, decreased health communication experience at certain moments when living in a hustle culture and known motives, namely because motives is social motives is productivity motives, self-confidence motives and objective motives (in-Order Motive), among others motives improvement in soft skills, networking and financial motives as well as a hustle culture which is interpreted by learning and practicing knowledge, maximizing one's time and potential, getting to know the world of work, feeling joy and proud. Keywords: Communication experiences, motives, meaning, hustle culture, students